3D-bioprinting of aortic valve interstitial cells: impact of hydrogel and printing parameters on cell viability. (1st January 2023) - Immohr, Moritz Benjamin; Dos Santos Adrego, Fabió; Teichert, Helena Lauren; Schmidt, Vera; Sugimura, Yukiharu; Bauer, Sebastian; Barth, Mareike; Lichtenberg, Artur; Akhyari, Payam
Abstract: Calcific aortic valve disease (CAVD) is a frequent cardiac pathology in the aging society. Although valvular interstitial cells (VICs) seem to play a crucial role, mechanisms of CAVD are not fully understood. Development of tissue-engineered cellular models by 3D-bioprinting may help to further investigate underlying mechanisms of CAVD. VIC were isolated from ovine aortic valves and cultured in Dulbecco's modified Eagle's Medium (DMEM). VIC of passages six to ten were dissolved in a hydrogel consisting of 2% alginate and 8% gelatin with a concentration of 2 × 10 6 VIC ml −1 . Cell-free and VIC-laden hydrogels were printed with an extrusion-based 3D-bioprinter (3D-Bioplotter ® Developer Series, EnvisionTec, Gladbeck, Germany), cross-linked and incubated for up to 28 d. Accuracy and durability of scaffolds was examined by microscopy and cell viability was tested by cell counting kit-8 assay and live/dead staining. 3D-bioprinting of scaffolds was most accurate with a printing pressure of P < 400 hPa, nozzle speed of v < 20 mm s −1, hydrogel temperature of T H = 37 °C and platform temperature of T P = 5 °C in a 90° parallel line as well as in a honeycomb pattern. Dissolving the hydrogel components in DMEM increased VIC viability on day 21 by 2.5-fold compared to regular 0.5% saline-based hydrogels ( p < 0.01). Examination at day 7 revealed dividing and proliferating cells. After 21 d the entire printed scaffolds were filled with proliferating cells. Live/dead cell viability/cytotoxicity staining confirmed beneficial effects of DMEM-based cell-laden VIC hydrogel scaffolds even 28 d after printing. By using low pressure printing methods, we were able to successfully culture cell-laden 3D-bioprinted VIC scaffolds for up to 28 d. Using DMEM-based hydrogels can significantly improve the long-term cell viability and overcome printing-related cell damage. Therefore, future applications 3D-bioprinting of VIC might enable the development of novel tissue engineered cellular 3D-models to examine mechanisms involved in initiation and progression of CAVD.